An empirical application of the median voter model and of the interest group influence model to the Portuguese and Galician municipalities - José Cruz (European Regional Science Association (ERSA), 2001)
The analysis of the median voter hypothesis indicates that a more realistic comprehension of local public choice might be achieved with the opening of the median voter model to the interst group influence hypothesis. A non-nested specification that combines the two models is estimated and its results are compared to the median voter model (MVM) and to the interest group influence model (IGM) results. The empirical analysis is developed for the Portuguese and the Galician municipalities. In addition, I tested the hypothesis of the relative political power of the median voter and of interest groups to vary with the dimension of the population of the municipalities. Finally, I analyse the existence of institutional and political differences between the two territories and their effects on the results. Fiscal illusion is compared for Portugal and Galicia.
Keywords: 330